L.O.T.E.: lugar, ocupação, tempo, espaço - Silva, Agnaldo Valente Germano da [UNESP]; Spaniol, José Paiani [UNESP]; Romagnolo, Sérgio Mauro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The University Extension Project titled L.O.T.E. – Lugar, Ocupação, Tempo, Espaço (Site, Occupation, Time, Space) - proposes a set of inter and transdisciplinary actions of space occupation, residence and living in Art and Art-Education. It is an initiative to invest in the experience of living propositions in Art as learning, in order to catalyze the maturation of the young artist and art-educator facing new challenging situations that instigate them to reorganize, practice, reflect and materialize with autonomy their learning in a collaborative sharing of artistic practices and art-education with the community.

O Projeto de Extensão Universitária intitulado L.O.T.E. – Lugar, Ocupação,Tempo, Espaço – propõe um conjunto de ações inter e transdisciplinares de ocupação do espaço, residência e vivência em Arte e Arte-Educação. Trata-se de uma iniciativa no sentido de investir em proposições de vivência em Arte como aprendizado, visando a catalisar o amadurecimento do jovem artista e arte-educador diante de novas situações desafiadoras que o instiguem a rearticular, praticar, refletir e materializar com autonomia seu aprendizado num compartilhamento colaborativo de práticas artísticas e arte/educativas com a comunidade.
Keywords: Artistic and art-education experience; Autonomy; Inter/transdisciplinary; Autonomia; Inter/transdisciplinaridade; Vivência artística e arte-educativa